A Computational Study of the Role of Secondary Metabolites for Mitigation of Acid Soil Stress in Cereals Using Dehydroascorbate and Mono-Dehydroascorbate Reductases - Shuvasish Choudhury; Muhammed Khairujjaman Mazumder; Debojyoti Moulick; Parul Sharma; Sandeep Kumar Tata; Dibakar Ghosh; Hayssam M. Ali; Manzer H. Siddiqui; Marian Brestic; Milan Skalicky; Akbar Hossain (MDPI AG, 2022)
The present study investigates the potential ameliorative role of seven secondary metabolites, viz., ascorbate (AsA), reduced glutathione (GSH), jasmonic acid (JA), salicylic acid (SA), serotonin (5-HT), indole-3-acetic acid (IAA) and gibberellic acid (GA3), for mitigation of aluminium (Al3+) and manganese (Mn2+) stress associated with acidic soils in rice, maize and wheat. The dehydroascorbate reductase (DHAR) and mono-dehydroascorbate reductase (MDHAR) of the cereals were used as model targets, and the analysis was performed using computational tools. Molecular docking approach was employed to evaluate the interaction of these ions (Al3+ and Mn2+) and the metabolites at the active sites of the two target enzymes. The results indicate that the ions potentially interact with the active sites of these enzymes and conceivably influence the AsA-GSH cycle. The metabolites showed strong interactions at the active sites of the enzymes. When the electrostatic surfaces of the metabolites and the ions were generated, it revealed that the surfaces overlap in the case of DHAR of rice and wheat, and MDHAR of rice. Thus, it was hypothesized that the metabolites may prevent the interaction of ions with the enzymes. This is an interesting approach to decipher the mechanism of action of secondary metabolites against the metal or metalloid - induced stress responses in cereals by aiming at specific targets. The findings of the present study are reasonably significant and may be the beginning of an interesting and useful approach towards comprehending the role of secondary metabolites for stress amelioration and mitigation in cereals grown under acidic soil conditions.